1994
DOI: 10.1017/s0025315400039382
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive pattern of the clams, Ruditapes decussatus and R. philippinarum on intertidal flats in Brittany

Abstract: Since the introduction of the Manila clam Ruditapes philippinarum (Mollusca: Bivalvia) to aquaculture clam beds, this species has spread to several sites. As a result, an extensive fishery has developed around this species. Its reproductive cycle and that of a native clam species, Ruditapes decussatus (Mollusca: Bivalvia) from two Brittany sites are examined here and the seasonal variations in the condition index, the scale of maturation stages, the histology and the oocyte size-frequencies of both species are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
40
0
15

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 10 publications
10
40
0
15
Order By: Relevance
“…g live weight -1 .day -1 ), permitted sexual maturation of Ruditapes decussatus. In all experiments normal gonadal development was observed, and was similar to that described by Laruelle et al (1994) and Rodríguez-Moscoso (2000) for R. decussatus during the reproductive cycle in natural populations. Our results have shown that the quantity of available food within the studied food range did not condition the gonadal development in this species, but modified some defining characteristics of gametogenesis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…g live weight -1 .day -1 ), permitted sexual maturation of Ruditapes decussatus. In all experiments normal gonadal development was observed, and was similar to that described by Laruelle et al (1994) and Rodríguez-Moscoso (2000) for R. decussatus during the reproductive cycle in natural populations. Our results have shown that the quantity of available food within the studied food range did not condition the gonadal development in this species, but modified some defining characteristics of gametogenesis.…”
Section: Discussionsupporting
confidence: 88%
“…However, there is currently no established relationship between food availability and gonadal development in R. decussatus or other Veneridae from the strictly histological point of view, despite abundant information concerning their reproductive cycle in natural populations (Pérez-Camacho, 1980;Beninger, 1982;Shaffee and Daoudi, 1991;Villalba et al, 1993;Xie and Burnell, 1994;Laruelle et al, 1994;Rodríguez-Moscoso, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…As gametogenesis is initiated at 12 • C in this species (Laruelle et al, 1994), clams from the three samples had empty gonads. Once in the laboratory, clams (37 to 50 mm length) were held in flow-through tanks in sieves containing field sediment.…”
Section: Biological Materials and Acclimation Proceduresmentioning
confidence: 90%
“…An increase of dry weight content started in March and coincided with an increase of temperature, Chl a, MICRO and especially NANO abundances. Laruelle et al (1994) also found that the maximum rate of increase in weight of Venerupis decussata occurs in the spring when both the sea temperature and food supply increase rapidly. Percent of dry weight of A. noae declined in May and July.…”
Section: Discussionmentioning
confidence: 86%